A new distributional model coupling environmental and biotic factors - Ruiz Barlett, Trinidad; Laguna, Maria Fabiana; Abramson, Guillermo; Monjeau, Jorge Adrian; Martin, Gabriel Mario (Elsevier Science, 2024)
Fil: Ruiz Barlett, Trinidad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fundación Bariloche; Argentina